Denitrifier communities differ in mangrove wetlands across China. (June 2020) - Li, Ruili; Wu, Sijie; Chai, Minwei; Xie, Shuguang
Abstract: To explore the geographical variations in the nosZ -denitrifier community and the underlying influential factors, surface sediments were collected from six mangroves across China, including Yunxiao (YX), Futian (FT), Fangchenggang (FCG), Zhanjiang (ZJ), Dongzhaigang (DZG), and Dongfang (DF). The nos Z gene abundance in mangrove sediments were 1.60 × 10 5 –1.17 × 10 6 copies g −1 dry sediment, with a higher density in Avicennia marina forest than the mudflat. Denitrifier community richness and diversity increased with decreasing latitude based on the Chao1 richness and Shannon diversity index, with the highest diversity being observed in the DF mangrove. The denitrifier communities could be classified into three groups including south DF mangrove, middle FCG, ZJ and DZG mangroves, and north YX and FT mangroves based on HCA and PCoA analysis. The nosZ OTUs could be divided into seven distinct clusters with different proportionality characteristics among mangroves. Environmental factors (TN, TOC, and salinity) collectively shape denitrifier communities in mangrove sediments. Graphical abstract: Unlabelled Image Highlights: Denitrifier communities in mangrove wetlands across China were firstly reported. Abundance, richness and diversity of denitrifier communities were geographic-related. The highest diversity of denitrifier community was observed in Dongfang mangrove. Denitrifier communities were not affected by Avicennia marina . Sediment carbon, nitrogen, and salinity collectively shaped denitrifier communities.